Pengaruh Religiusitas Kepercayaan dan Kemudahan terhadap Minat Bersedekah via Kitabisa.com - Puspita, Ayu; Yunus, Ayu Ruqayyah; Sofyan, A. Syathir (Darul Yasin Al Sys, 2024)
In the midst of the government's less than optimal role in reducing poverty in Indonesia, the birth of many fundraising platforms (Crowdfunding) which are engaged in social and are able to become media in carrying out social fundraising properly, Crowdfunding is a fundraising activity that can be used to raise money from the community then distributed to those in need. This research is a research using a quantitative approach. The population of this study is people who have used Kitabisa.com at least once. The sampling technique used nonprobability sampling with purposive sampling, the number of samples was 277 respondents. The data analysis technique used is the Classical Assumption Test, and Hypothesis Testing using the SPSS 21 program. The results of this study indicate that: 1) Religiosity has a positive and significant effect on Interest in Giving Alms Via Kitabisa.com. 2) Trust has a positive and significant effect on interest in giving alms via Kitabisa.com. 3) Convenience has a positive and significant effect on interest in giving alms via Kitabisa.com.